Financial Education: A study involving the students of a higher education institution of the city Divinopolis in Minas Gerais (Research, Society and Development, 2019)
Financial education is a process in which people can improve and develop necessary knowledge that will contribute to better decision making. This study analyzes if the level of knowledge acquired by the undergraduate students, throughout the course, make them better decisions-makers, concerning financial investments. Also, if the students of Accounting and Business are more assertive in their choices, besides testing variable such as gender, age, income and marital status. To test the hypothesis raised, a questionnaire was applied in a sample of 50% of the population of a faculty of Divinopolis, corresponding to 395 students. The results are categorized and demonstrate that the fact that the students are in the first or last terms, the faculty and the variables chosen have no influence on the level of financial knowledge or the assertiveness of the investment choices.